Minimally invasive versus open pelvic exenterations for rectal cancer: a comparative analysis of perioperative and 3-year oncological outcomes. Issue 5 (14th September 2021) - Kazi, M; Kumar, N A N; Rohila, J; Sukumar, V; Engineer, R; Ankathi, S; Desouza, A; Saklani, A
Abstract: Background: This study compared the surgical and oncological outcomes of open and minimally invasive pelvic exenteration. Methods: Patients who underwent pelvic exenterations for primary locally advanced rectal cancers with invasion of the urogenital organs (central and anterior disease) between August 2013 and September 2020 were reviewed retrospectively. Patients were categorized as undergoing open or minimally invasive surgery (MIS) and these groups were compared for perioperative outcomes and 3-year survival (overall, recurrence-free and local relapse-free survival). Multivariable Cox regression analysis was performed to assess the independent influence of approach of surgery and cancer features on recurrence-free survival (RFS). Results: Of the 158 patients who underwent pelvic exenteration, 97 (61.4 per cent) had open exenterations and 61 (38.6 per cent) patients had an MIS resection (44 patients (72 per cent) using laparoscopy and 17 (28 per cent) using robotic surgery). There were 96 (60.8 per cent) total pelvic exenterations and 62 (39.2 per cent) posterior pelvic exenterations. MIS exenterations had significantly longer operative times (MIS versus open: 640 mins versus 450 mins; P < 0.001) but reduced blood loss (MIS versus open: 900 ml versus 1600 ml; P < 0.001) and abdominal wound infections (MIS versus open: 8.2 versus 17.5 per cent; P = 0.020) without a difference in hospital stay (MIS versus open: 11 versus 12 days; P = 0.620). R0 resection rates and involvement of circumferential resection margins were similar (MIS versus open: 88.5 versus 91.8 per cent, P = 0.490 and 13.1 versus 8.2 per cent, P = 0.342 respectively). At a median follow-up of 29 months, there were no differences in 3-year overall survival (MIS versus open: 79.4 versus 60.2 per cent; P = 0.251), RFS (MIS versus open: 51.9 versus 47.8 per cent; P = 0.922) or local relapse-free survival (MIS versus open: 89.7 versus 75.2 per cent; P = 0.491. On multivariable analysis, approach to surgery had no bearing on RFS, and only known distant metastasis, aggressive histology and inadequate response to neoadjuvant radiation (pathological tumour regression grade greater than 3) predicted worse RFS. Conclusion: MIS exenterations documented longer procedures but resulted in less blood loss and fewer wound infections compared with open surgeries. In the setting of an experienced centre, the hospital stay, R0 resection rates and oncological outcomes at 3 years were similar to those of open exenterations. Abstract : Minimally invasive exenterations are oncologically safe operations for primary rectal cancers in specialized centres, with outcomes comparable to those of open exenterations. Minimally invasive surgeries were associated with longer operative times but reduced blood loss and abdominal wound infections.